2003
DOI: 10.1046/j.1464-410x.2003.03057.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cyclooxygenase‐2 in high‐grade human transitional cell carcinoma of the upper urinary tract

Abstract: OBJECTIVE To examine cyclooxygenase (COX)‐2 expression (a key enzyme in the synthesis of prostaglandins, and involved in carcinogenesis of human epithelial tumours) in human transitional cell carcinomas (TCCs) of the renal pelvis and ureter, and to determine whether COX‐2 expression correlates with the clinicopathological characteristics of the disease. MATERIALS AND METHODS Specimens from 144 patients with TCC of the upper urinary tract who had undergone nephroureterectomy were analysed immunohistochemically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…It may be hypothesized that COX‐2 overexpression is involved in the initiation process of carcinogenesis, as shown previously [14,23], but, once tumours have reached a level of aggressiveness (such as in the invasive bladder cancer cases of the present study), the maintenance of COX‐2 expression may be associated with tumours presenting a better prognosis. Furthermore, the evolution of expression of COX‐2 from NMIBT to invasive bladder tumours, compared to tumours that are invasive upfront, is not established and may have contributed to the results obtained.…”
Section: Discussionsupporting
confidence: 71%
“…It may be hypothesized that COX‐2 overexpression is involved in the initiation process of carcinogenesis, as shown previously [14,23], but, once tumours have reached a level of aggressiveness (such as in the invasive bladder cancer cases of the present study), the maintenance of COX‐2 expression may be associated with tumours presenting a better prognosis. Furthermore, the evolution of expression of COX‐2 from NMIBT to invasive bladder tumours, compared to tumours that are invasive upfront, is not established and may have contributed to the results obtained.…”
Section: Discussionsupporting
confidence: 71%
“…6,7 Several studies have demonstrated that COX-2 is involved in the development of many tumors by affecting biological features including proliferation, angiogenesis, apoptosis, and adhesion, [9][10][11] and that COX-2 specific inhibitors actually reduce the incidence of development of tumors in animals 12 as well as in humans. 13 The expression of COX-2 is up-regulated in both transitional [14][15][16] and squamous 17 cell carcinoma of the human urothelial tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The higher expression level of COX-2 has been shown to increase invasiveness in colon cancer and prostate cancer cells (24,39). For UUTUC, overexpressed COX-2 was also found in patients and was associated with the pathologic stage and grade, indicating that COX-2 may be involved in UUTUC carcinogenesis and development (40,41). The effect of the specific COX-2 inhibitor on AR-enhanced migration and invasion clearly demonstrated the essential role of COX-2 in cell migration and invasion ( Fig.…”
Section: Discussionmentioning
confidence: 98%